Strategies for Overcoming Difficulties in Learning Mathematics - Febriani, Nur Indah; Elfrianto, Elfrianto (EDUCTUM: Journal Research, 2023)
Mathematics is a basic science that can be used to solve problems in many other fields of science. However, the fact is that there are still many mathematics learning activities in the field that cause a higher level of learning difficulty than other subjects. Students' inability to complete assignments given by the teacher can also be interpreted as learning difficulties. Students also believe that mathematics is a difficult subject to learn. In accordance with the causal factors, a learning problem solving strategy is an approach chosen and used by an educator to deliver lesson material with the aim of making it easier for students to accept and understand the material and ultimately achieve learning goals.